Coping with dyspareunia, the importance of inter and intrapersonal context on women's sexual distress: a population-based study - Ameneh Alizadeh; Farnaz Farnam (BMC, 2021)
Plain English summary Dyspareunia is a condition that can negatively affect sexual health among individuals and couples. This paper addresses the pattern of sexual pain as well as some interpersonal and intrapersonal factors that may lessen sexual pain by mitigating sexual distress. This population-based cross-sectional study was conducted on 590 randomly selected Iranian married women aged 18-70 years. According to the research results, the prevalence of self-report sexual pain was 33 %. However, based on strict Binik's criteria and sexual distress, the prevalence of severe Dyspareunia decreased to 10.5 %. The most common location, time, and type of pain were reported to be in the vaginal entrance at the beginning of intercourse with irritation. Interestingly, a substantial number of women reported no sexual distress, despite having severe Dyspareunia. Compared to patients with distress, they experienced higher levels of sexual satisfaction, more positive body images, higher levels of self-confidence, and more intimacy in their relationships (P = .000). In addition to the routine management of sexual pain, clinicians should consider these protective factors that can lead to better pain tolerance and less sexual distress among patients. The research findings emphasized the importance of attendance and collaboration of spouses in the treatment process. At the same time, observing the sexual distress of women with no sexual dysfunctions would clarify that their own perception of sexual difficulty per se is an important factor. In other words, "sexual dysfunction" and "sexual problems" are both significant because defining sexual problems is subjective and depends on a woman and her partner's values, desires, and sexual knowledge.